Product sophistication and spillovers from foreign direct investment. (November 2016) - Eck, Katharina; Huber, Stephan
Abstract: Foreign direct investment (FDI) in developing countries is often associated with higher economic growth due to knowledge and technology spillovers to local firms. One way that FDI speeds up growth is by facilitating the manufacturing of more sophisticated products by local firms. So far, there is a lack of firm‐level evidence how the presence of multinational firms affects the product sophistication of firms in a developing country. The aim of this paper is to fill this gap. We compile an extensive firm–product‐level data set of Indian manufacturing firms, which we complement with information on product sophistication and spillovers from FDI. We then explore different channels through which spillovers from multinationals to local Indian firms foster the manufacturing of sophisticated products. We find evidence that spillovers through supplier linkages strongly increase the manufacturing of sophisticated products in India.